The Effect of Implementing a Nursing Action Strategy on Client's Hallucinations on the Ability to Control Hallucinations. - Nurul Rezeki Rahmadhani; Narmi Narmi; Tahiruddin Tahiruddin (KLASICS, 2022)
Introduction Hallucinations are the loss of human ability to distinguish between internal stimuli (thoughts) and external stimuli (the outside world). Clients give perceptions or opinions about the environment without real objects or stimuli such as clients who listen to voices when no one is talking. The World Health Organization (WHO) reports that in 2018, there were about 300 million people (21%) affected by depression, 60 million people (36%) were affected by bipolar, and 23 million people (12%) were affected by schizophrenia, 50 million people. The purpose of this study was to determine the effect of implementing strategies for implementing client hallucinations on the ability to control auditory hallucinations at the Mental Hospital of Southeast Sulawesi Province. Method This study used a quasi-experimental design (pre-experimental) one group pretest-posttest design, the population of all patients with auditory hallucinations was 97 people, and a sample of 49 people who met the criteria with a simple random sampling technique located at the Mental Hospital of Southeast Sulawesi Province in August April to May 2020. Results From the results of the Wilcoxon test, it was found that the deviation value before and after the implementation of the implementation strategy in controlling hallucinations was that there was increased before and after the implementation strategy was given, the value was 0.000 < 0.05, then H1 was accepted, which means that there is an influence on the implementation of the strategy for implementing nursing actions. client hallucinations on the ability to control auditory hallucinations. Conclusion There is an implementation strategy for implementing corrective actions for clients on the ability to control hearing so that researchers are expected to become nurses' knowledge about the client's ability to control hearing experienced during the recovery process